2014
DOI: 10.1111/eip.12129
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy for adolescents and young adults at high risk for psychosis: a systematic review

Abstract: Evidence from recent trials suggest that cognitive behaviour therapy may be beneficial in delaying or preventing onset of psychosis in clinical high-risk individuals, although effect sizes to date appear small. Further research is needed in larger samples to establish whether cognitive behaviour therapy is efficacious, and if additional intervention components can enhance established psychotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 82 publications
1
36
0
Order By: Relevance
“…Given the wide range of clinically relevant difficulties endorsed by individuals at CHR, in addition to research indicating that early intervention may be effective for reducing psychosis-related symptomatology and preventing or delaying transition to psychosis (van der Gaag et al, 2013;Okuzawa et al, 2014), efforts to develop and refine flexible and wide-reaching treatment protocols for individuals at CHR seem warranted. Interventions that take a flexible approach to treatment could provide a model of care that can be tailored to the unique and dynamic needs of individuals at CHR by offering clinicians an array of evidence-based modules to use as needed to address psychosisspecific symptoms as well as co-occurring difficulties (Thompson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the wide range of clinically relevant difficulties endorsed by individuals at CHR, in addition to research indicating that early intervention may be effective for reducing psychosis-related symptomatology and preventing or delaying transition to psychosis (van der Gaag et al, 2013;Okuzawa et al, 2014), efforts to develop and refine flexible and wide-reaching treatment protocols for individuals at CHR seem warranted. Interventions that take a flexible approach to treatment could provide a model of care that can be tailored to the unique and dynamic needs of individuals at CHR by offering clinicians an array of evidence-based modules to use as needed to address psychosisspecific symptoms as well as co-occurring difficulties (Thompson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the mental health needs of those with CHR symptoms (regardless of conversion) may help inform assessment and treatment. This is particularly relevant as individuals at CHR have a present need for treatment, and that early intervention is likely beneficial for long-term outcomes (Fusar-Poli 2012; Morrison et al, 2012;Preti and Cella, 2010;Stafford et al, 2013;Okuzawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this obvious need for treatment, an increasing number of interventions have been evaluated in CHR samples in recent years [97,89,109]. With the primary goal of preventing conversion to psychosis, these studies have drawn upon wellestablished interventions for adult schizophrenia patients and used conversion to psychosis as their primary outcome [63,68,75].…”
Section: Requirements For Early Intervention Approachesmentioning
confidence: 99%
“…Although several ongoing clinical trials aim to establish treatment protocols for youths with prodromal symptoms (13,14), practice guidelines for CHR individuals emphasize watchful waiting. This study had several limitations, chiefly the small sample and limited duration of follow-up (larger studies of CHR youths have found that conversion to psychosis may take place several years after initial presentation of attenuated positive symptoms, thus necessitating a potentially longer period of clinical monitoring).…”
Section: Discussionmentioning
confidence: 99%